EFFECTIVENESS OF INTEGRATED READING AND COOPERATIVE MODELS OF COMPOSITION (CIRC) IN LEARNING TO READ LITERARY WORKS - Asrul, Asrul; Rizal, Awaluddin (Universitas Khairun, 2025)
Reading literary works is one of the art activities that must be carried out continuously. To support literary reading activities, students and lecturers play a crucial role in selecting a learning model that fosters literary reading. Learning to read literary works, the application of the Cooperative Integrated Reading and Composition (CIRC) model is one effective approach to learning to read, particularly literary works. This study aims to determine the effectiveness of the CIRC model in learning to read literary works in the Literary Appreciation course. This study uses a quasi-experimental design by comparing two learning models, namely the conventional model and the CIRC model. The subjects of this study were fourth-semester students of the Faculty of Teacher Training and Education (FKIP) at Khairun University in North Maluku, Indonesia. The results of this study indicate that the use of the Cooperative Integrated Reading and Composition (CIRC) Model is effective in supporting literary reading activities in the literary appreciation course.